Kampung Halaman bagi Perantau dalam Cerpen "Bagaimana Sebuah Kampung" Menuju Kematiannya Karya Sandi Firly - Sugiarto, Septian Rifki (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2024)
The relationship between migrants and their hometown is often depicted in literary works. One of the literary works that depicts this phenomenon is the short story “Bagaimana Sebuah Kampung Menuju Kematiannya” by Sandi Firly. The purpose of this study is to explain the perception of migrants towards their hometown. With this study, it is hoped that it can be known how migrants who have been away for a long time and settled in big cities see and interpret their hometowns. This study is a qualitative study using a sociology of literature approach. Data collection was carried out by recording and analyzing the data using content analysis. The results of this study indicate that the hometown, namely Kuala Pembuang for migrants like Hasan, has a deep meaning and a special place that is impossible to replace at any time. Big cities with all their attractive offers will never be able to erase a migrant’s love for their hometown.